ENHANCED WOUND HEALING USING ANTHOCYANIN-LOADED SILK SERICIN/POLYVINYL ALCOHOL NANOFIBERS: A BIOMATERIAL-BASED APPROACH - JAJNADATTA PANDA; ABHISEK PAL; PRITIPADMA PANDA; ARCHANA PANIGRAHY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The goal of this study was to create a nanofibrous wound dressing using silk sericin (SS) and polyvinyl alcohol (PVA) that included anthocyanin (ACN) phytoconstituents in different amounts to promote wound healing, pH monitoring, and antibacterial activity. Methods: PVA–SS–ACN nanofibers were created by electrospinning with varying concentrations of solution (A1, A4, and A5), yielding average fiber diameters of 144.13 nm, 169.15 nm, and 192.51 nm, respectively. Up to 85 h of continuous herbal ingredient release was demonstrated by the nanofibers’ bead-free shape. Through structural and thermal characterizations using scanning electron microscopy, Fourier transform infrared, and thermogravimetric analysis, the stability of the nanofibrous mats up to 50°C, the chemical integration of ACNs, and the creation of smooth fibers were all confirmed. Results: The most potent antibacterial action against Staphylococcus aureus and Escherichia coli was shown by the nanofibrous mat loaded with 0.1 and 1% w/w ACN. In this study, the comparison between 0.1 and 1% the therapeutic efficacy is higher in 1% because the dose of the drug increased. Histological and in vivo wound healing investigations demonstrated superior healing efficiency, reduced acute and chronic inflammation, and accelerated tissue regeneration compared to untreated control groups. Conclusion: The PVA–SS–CAN nanofibrous dressing’s remarkable antibacterial, anti-inflammatory, and controlled drug-release qualities make it a promising option for advanced wound healing applications. The interwoven network of fibers also aids in exudate control, reducing the discomfort of dressing changes by absorbing excess fluid and preventing the dressing from adhering to the wound.